Regional Financial Management Towards Village Development Independency in Indonesia Lacking Regions - ., Suyanto; Almughni, Muhammad Afdha Alif; Standsyah, Rahmawati Erma; Mustofa, Amirul; Haryati, Eny; Ramadhan, Dendy Syahru; Possumah, Bayu Taufiq (Journal of Ecohumanism, 2024)
The aim of this study is to examine the impact of regional government expenditure on regional autonomy, taking into account indices of social, economic, and ecological resilience within the context of impoverished regions. This study employs panel regression and route analysis techniques to analyze data from 62 districts identified as undeveloped regions in Indonesia throughout the period of 2016–2022. The exogenous factors in this study encompass capital investment, operating expenditure, and balancing funds, whereas the endogenous variable is the village development index. The findings show that (1) capital expenditure, operational expenditure, and balancing funds have an indirect influence on IDM through the economy. (2) Capital expenditure has a negative impact on economic growth because underdeveloped areas are increasingly concentrated in the eastern region and cause economic disparities to grow. (3) Operational expenditure and balancing funds have a positive impact on the regional economy, which also impacts village independence.